YWHAG inhibits influenza a virus replication by suppressing the release of viral M2 protein - Mao, Haiying; Cao, Lei; Xu, Ting; Xia, Xiaohan; Ren, Peilei; Han, Pengfei; Li, Chengfei; Hui, Xianfeng; Lin, Xian; Huang, Kun; Jin, Meilin (Frontiers in Microbiology, 2022)
Influenza A virus (IAV) poses a serious threat to human life and property. The IAV matrix protein 2 (M2) is significant in viral budding. Increasing studies have proven the important roles of host factors in IAV replication. In this study, immunoprecipitation combined with mass spectrometry revealed that the host protein tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein gamma (YWHAG), which belongs to the 14-3-3 protein scaffold family, interacts with M2. Their interactions were further confirmed by co-immunoprecipitation (Co-IP), immunofluorescence, and confocal microscopy of virus-infected HeLa cells. Moreover, we constructed YWHAG-KO and YWHAG-overexpressing cells and found that YWHAG knockout significantly increased viral production, whereas its overexpression reduced the titer of virus progeny. Therefore, YWHAG is a negative regulatory factor during IAV infection. Further, YWHAG knockout or overexpression had no effect on the binding, entry, or viral RNA replication in the early stages of the virus life cycle. On the contrary, it impaired the release of virions at the plasma membrane as determined using transmission electron microscopy and suppressed the M2-mediated budding of the influenza virus. Importantly, the H158F mutation of YWHAG was found to affect interaction with M2 and its budding. Collectively, our work demonstrates that YWHAG is a novel cellular regulator that targets and mediates the interaction and release of M2.